A nano-carrier platform for the targeted delivery of nature-inspired antimicrobials using Engineered Water Nanostructures for food safety applications. (February 2019) - Vaze, Nachiket; Pyrgiotakis, Georgios; Mena, Lucas; Baumann, Robert; Demokritou, Alexander; Ericsson, Maria; Zhang, Yipei; Bello, Dhimiter; Eleftheriadou, Mary; Demokritou, Philip
Abstract: Despite the progress in the area of food safety, foodborne diseases still represent a massive challenge to the public health systems worldwide, mainly due to the substantial inefficiencies across the farm-to-fork continuum. Here, we report the development of a nano-carrier platform, for the targeted and precise delivery of antimicrobials for the inactivation of microorganisms on surfaces using Engineered Water Nanostructures (EWNS). An aqueous suspension of an active ingredient (AI) was used to synthesize iEWNS, with the 'i' denoting the AI used in their synthesis, using a combined electrospray and ionization process. The iEWNS possess unique, active-ingredient-dependent physicochemical properties: i) they are engineered to have a tunable size in the nanoscale; ii) they have excessive electric surface charge, and iii) they contain both the reactive oxygen species (ROS) formed due to the ionization of deionized (DI) water, and the AI used in their synthesis. Their charge can be used in combination with an electric field to target them onto a surface of interest. In this approach, a number of nature-inspired antimicrobials, such as H2 O2, lysozyme, citric acid, and their combination, were used to synthesize a variety of iEWNS-based nano-sanitizers. It was demonstrated through foodborne-pathogen-inactivation experiments that due to the targeted and precise delivery, and synergistic effects of AI and ROS incorporated in the iEWNS structure, a pico-to nanogram-level dose of the AI delivered to the surface using this nano-carrier platform is capable of achieving 5-log reductions in minutes of exposure time. This aerosol-based, yet 'dry' intervention approach using iEWNS nano-carrier platform offers advantages over current 'wet' techniques that are prevalent commercially, which require grams of the AI to achieve similar inactivation, leading to increased chemical risks and chemical waste byproducts. Such a targeted nano-carrier approach has the potential to revolutionize the delivery of antimicrobials for sterilization in the food industry. Highlights: A novel antimicrobial platform using Engineered Water Nanostructures (EWNS) is presented. The iEWNS platform delivers nanogram levels of known antimicrobials in a targeted and efficient way. Five-log reductions of E. coli by iEWNS produced with hydrogen peroxide, citric acid, and lysozyme. Microbial inactivation due to the synergistic effect of generated ROS & antimicrobial. Mechanism of inactivation is cell-envelope and intracellular processes interference.